Small interfering RNA: potential in real-world clinical practice - A. S. Motrinchuk; A. R. Kasimova (Реальная клиническая практика: данные и доказательства)
This review describes the basics of protein biosynthesis and RNA interference processes, discusses the useful and unique properties of siRNA therapy, its advantages and disadvantages in comparison with other gene silencing methods, provides a brief overview of technical advances and modifications of siRNA therapy, and characterizes siRNA-registered drugs and agents at different stages of clinical trials.